Output, Employment, and Wages in the Short Run - Solow, Robert M.; Stiglitz, Joseph E. (Quarterly Journal of Economics, 1968)
I. Introduction, 537.–II. Building blocks, 539.–III. The working of the model, 545.–IV. Displacement of short-run equilibrium, 554.–V. Effective demand and the distribution of income, 557.–VI. Next steps, 559.